2015
DOI: 10.5603/fm.2015.0112
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of increased axillary blood flow velocity without increased handgrip strength and endurance in persons with a fibromuscular axillary arch

Abstract: (Folia Morphol 2015; 74, 4: 486-492)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous study [53] has found that 30 times/ minute of grip exercise can effectively improve venous blood flow, which is the best frequency of grip exercise after PICC. In addition, a study [54] has found that the patient's use of the grip ball in the palm of the hand can give the patient a sense of reality, enhance the afterload of the upper arm muscle group contraction, and effectively promote blood At the same time, some studies [55,56] believe that the use of electronic grips to guide patients to make fist exercises can enhance the effect of grip exercises. When the frequency of electronic grips is 25 times/minute and the exercise duration is 2 minutes, the blood flow and speed of patients can reach the maximum, this maximizes patient benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study [53] has found that 30 times/ minute of grip exercise can effectively improve venous blood flow, which is the best frequency of grip exercise after PICC. In addition, a study [54] has found that the patient's use of the grip ball in the palm of the hand can give the patient a sense of reality, enhance the afterload of the upper arm muscle group contraction, and effectively promote blood At the same time, some studies [55,56] believe that the use of electronic grips to guide patients to make fist exercises can enhance the effect of grip exercises. When the frequency of electronic grips is 25 times/minute and the exercise duration is 2 minutes, the blood flow and speed of patients can reach the maximum, this maximizes patient benefit.…”
Section: Discussionmentioning
confidence: 99%